Expression of thrombin-activatable fibrinolysis inhibitor (TAFI) is up-regulated by increase in intracellular cyclic AMP levels in cultured HepG2 cells - Ishii, Hidemi; Kojima, Yuka; Masuda, Yutaka; Takada, Kimihiko; Sugimoto, Katsuyoshi; Ikeda, Tomohiro (Thrombosis and Haemostasis, 2009)
Thrombin-activatable fibrinolysis inhibitor (TAFI), a carboxypeptidase B-like proenzyme, is predominantly biosynthesised in the liver and released into circulating plasma. Activated TAFI has a role in maintaining the balance between blood coagulation and fibrinolysis. We investigated the regulation of TAFI expression in cultured human hepatoma HepG2 cells. Stimulation of the cells with forskolin and dibutyryl cyclic AMP (DBcAMP) increased TAFI antigen levels in the cells in parallel with TAFI mRNA levels and antigen release from the cells into the conditioned medium. The elevated TAFI expression was abolished by pretreatment of the cells with KT5720, a protein kinase A (PKA) inhibitor. The promoter activity of the TAFI gene and the half-life of the TAFI transcript in DBcAMP-stimulated HepG2 cells increased to 1.5-fold and 2.0-fold, respectively, of those in the control cells. The increased promoter activity and the prolonged half-life were abolished by pretreatment of the cells with KT5720.These results suggest that an increase in intracellular cAMP levels upregulates TAFI expression in the cells in accompaniment with an elevation of TAFI mRNA levels, and that the elevated mRNA levels are derived from both transcriptional and post-transcriptional regulations of the TAFI gene mediated by activation of the AMP/PKA signaling pathway.
Keywords: Thrombin-activatable fibrinolysis inhibitor (TAFI); TAFI mRNA stability; cyclic AMP; protein kinase A; TAFI promoter activity